Collaboration in caring for psychiatric inpatients: Family physicians team up with psychiatrists and psychiatric nurses - Behroozi, Dara (College of Family Physicians of Canada, 2008)
PROBLEM BEING ADDRESSED: The standard organization of psychiatric inpatient care at our hospital involved consultations with various specialist physicians visiting the psychiatry wards to assess patients’ medical needs and to provide appropriate interventions. We thought that this type of clinical care pathway might not be leading to the best integration and timeliness of patient care, the most efficient use of specialist resources, or the least cost to the health care system. OBJECTIVE OF PROGRAM: To initiate a protocol that would involve an FP visiting all the psychiatry wards daily (on weekdays) to conduct medical consultations. We hoped this program would improve the timeliness and integration of patient care, reduce patients’ length of stay in hospital, and alter the pattern of specialist consultations. PROGRAM DESCRIPTION: The FP consulted on patients referred by psychiatrists and registered psychiatric nurses; carried out assessments; initiated treatment of common medical problems; referred to other specialists when necessary; and made arrangements for follow-up care as appropriate. CONCLUSION: The FP consultations improved patient care in several ways, was highly valued by staff, and modified the pattern of specialist consultations on participating psychiatry wards.